THEMATIC PROGRESSION VARIATION OF THE GREAT GATSBY ENGLISH-BAHASA INDONESIA TRANSLATIONAL TEXTS - Emi Nursanti; Asruddin Barori Tou (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2014)
The data-based research on which this article is based aimed at (1) describing the thematic progression variation of The Great Gatsby texts, (2) describing the contextual factors that motivate the variation in question, and (3) describing the effects of the variation on the texts as translational texts. The study applied a qualitative approach which employed a sematic-translational content analysis of qualitative and quantiative data. The results show that thematic progression variation falls into the low category at average indicated by the mean score of 0.76. The most prominent variation was repre-sented by the low category of variation. The variations were performed by adding or omitting Themes, splitting one units of thematic structure into more than one unit, downranking, not expressing and creating new clauses. The factors that motivate the variation are the different linguistic properties bet-ween English and Bahasa Indonesia and the situational contexts. In terms of effects, the variation caused dangling clauses which cannot be identified from which they are developed.Keywords: thematic progression, thematic structure, Theme, Rheme